2006
DOI: 10.2215/cjn.01271005
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Renal Diseases Associated with Extreme Forms of Insulin Resistance

Abstract: Diabetic nephropathy is the leading cause of ESRD in the United States. Why the pathogenic mechanisms lead to nephropathy in certain patients with type 1 and 2 diabetes and spare others is unclear, but it is clear that hyperglycemia and glomerular hyperfiltration are important factors. In patients with syndromes of extreme insulin resistance, proteinuric forms of renal disease are common, but it is surprising to find that the renal pathology usually is not diabetic nephropathy. For instance, in the lipodystrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 40 publications
(36 reference statements)
0
36
0
Order By: Relevance
“…The improvement in glucose tolerance occurred even though most patients had a reduction in their glucose-lowering medications (Table 3). Effect of leptin on urinary protein We have previously reported that generalised lipodystrophy can be associated with clinical and nephrotic-range proteinuria and that this proteinuria can be ameliorated with leptin therapy [12,13]. The decrease in proteinuria with leptin replacement is accompanied by a reduction in creatinine clearance and hyperfiltration [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The improvement in glucose tolerance occurred even though most patients had a reduction in their glucose-lowering medications (Table 3). Effect of leptin on urinary protein We have previously reported that generalised lipodystrophy can be associated with clinical and nephrotic-range proteinuria and that this proteinuria can be ameliorated with leptin therapy [12,13]. The decrease in proteinuria with leptin replacement is accompanied by a reduction in creatinine clearance and hyperfiltration [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Effect of leptin on urinary protein We have previously reported that generalised lipodystrophy can be associated with clinical and nephrotic-range proteinuria and that this proteinuria can be ameliorated with leptin therapy [12,13]. The decrease in proteinuria with leptin replacement is accompanied by a reduction in creatinine clearance and hyperfiltration [12,13]. In six patients, the nature of the renal dysfunction was determined by renal biopsy [13]; however, the specific aetiology of proteinuria was not known for the majority of patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations